Experimental study of the influence of selected technological casting parameters on structure and mechanical properties of steel castings - Bakošová, Dana; Bakošová, Alžbeta (Manufacturing Technology Journal, 2020)
The aim of the work was to assess influence of technological parameters of casting on thickness and continuity of decarburized layer of castings and their mechanical characteristics in order to suggest adjustment in the production process according to discovered results. The samples for experimental work were taken from one type of casting made from steel 42CrMo4. The thickness of decarburized layer was examined on the samples cast at different temperatures of ceramic mould and at different temperatures of casting. Influence of the wall thickness of the casting was also evaluated. It was ob-served that changing temperature of the ceramic mould does not cause a significant change in the decarburized surface area of the casting. The influence of the casting temperature of the metal and the shape of the casting is more pronounced in the formation of the decarburized surface layer. As the casting temperature rises, the thickness of the decarburized surface layer of the casting increases. With the increasing wall thickness of the casting, the surface decarburization layer also gets thicker.
Keywords: Alloy; Casting; Ceramic form; Decarburized layer